Hubungan Stres Akademik dan Kecanduan Game Online: Studi Korelasional pada Siswa SMAN 1 Baso - Jannah, Intan Miftahul; Hariko, Rezki (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study aims to examine the relationship between academic stress and online gaming addiction among high school students. The research involved 258 students from SMAN 1 Baso, selected through a stratified random sampling technique. A quantitative approach with a correlational method was employed. The instruments used were the Academic Stress Scale and the Online Gaming Addiction Scale, both of which had been tested for validity and reliability. Data were analyzed using the Pearson Product-Moment correlation test with the help of SPSS version 20.0 for Windows. The results indicated that students' academic stress levels were in the moderate category (56.08%), while their online gaming addiction levels were also moderate (57.11%). Correlation analysis revealed a significant positive relationship between academic stress and online gaming addiction (r = 0.356; p < 0.05). This indicates that the higher the level of academic stress experienced by students, the higher their tendency toward online gaming addiction. These findings are expected to serve as a foundation for school counselors and educational institutions in designing prevention and intervention programs to reduce both academic stress and online gaming addiction among students.